Is curtobacterium wilt biocontrol temperature dependent? - Martins, Samuel Julio; Medeiros, Flavio Henrique Vasconcelos; Souza, Ricardo Magela; Vilela, Laize Aparecida Ferreira (Acta Scientiarum. Agronomy, 2014)
Abiotic stress interferes with plant-microbial interactions, but some microorganisms may buffer this interference. We investigated the interaction between temperature and bacterial wilt (Curtobacterium flaccumfaciens pv. flaccumfaciens - Cff) biocontrol and the ability of Bacillus subtilis strain ALB629 to colonize bean seedlings, to inhibit pathogen growth and to use different C and N sources. B. subtilis ALB629rif, a mutant selected from the wild population of ALB629, was used to monitor plant colonization at 20°C and 30°C. ALB629rif was detected only in the plant roots (103.22 CFU g-1) at the lower temperature but colonized the roots, stems, and leaves (105.85, 104.48, and 104.01 CFU g-1), respectively, at 30ºC. The area under the disease progress curve was also different at the two tested temperatures (p < 0.01). Nevertheless, the disease reduction using ALB629rif - treated seeds was similar: 71% and 75%, respectively, at 20 and 30ºC (p < 0.01). A higher efficiency of C and N source utilization was observed at the higher temperature, but the antagonist inhibited Cff growth equally at either temperature in vitro. Based on our results, temperature interferes with pathogen and antagonist plant colonization, but the overall suppression of bacterial wilt appears to be stabilized by ALB629.